SCOLIOSIS IN CHILDREN: A STRUCTURED APPROACH TO PHYSIOTHERAPEUTIC ASSESSMENT - Лістау, Карина; Толок, Віктор (SWorldJournal, 2025)
Early and thorough physiotherapeutic assessment plays a crucial role in the management of scoliosis in children. According to modern clinical guidelines and international standards of physical therapy practice (ISCO-08), a comprehensive examination is the